A novel LC–MS/MS assay to quantify dermatan sulfate in cerebrospinal fluid as a biomarker for mucopolysaccharidosis II. (4th June 2018) - Pan, Peng; Chen, Mu; Zhang, Zhiling; Corte, Amauri Dalla; Souza, Carolina; Giugliani, Roberto; Pan, Luying; Qiu, Yongchang; Amaravadi, Lakshmi; Wu, Jiang
Aim: The study aimed to develop an LC–MS/MS assay to measure dermatan sulfate (DS) in human cerebrospinal fluid (CSF).Methods & results: DS was quantified by ion pairing LC–MS/MS analysis of the major disaccharides derived from chondroitinase B digestion. Artificial CSF was utilized as a surrogate for calibration curve preparation. The assay was fully validated, with a linear range of 20.0–4000 ng/ml, accuracy within ±20%, and precision of ≤20%. CSF samples from mucopolysaccharidoses (MPS) II patients showed an average of 11-fold increase in DS levels compared with controls.Conclusion: The described assay is capable of differentiating DS levels in the CSF of MPS II patients from controls and can be used to monitor disease progression and therapeutic responses.